IBM Incorporated : an exploration of an Egyptian work ethic as constructed by South African expatriates working in Cairo - Van Wyk, Milandre Heidi (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.